Call admission on the uplink and downlink of a CDMA system based on total received and transmitted powers. - Aissa, S.
We consider the problem of call admission and resource management in a code-division multiple-access (CDMA) wireless network supporting several types of services over a range of transmission rates and offering possibly different grades of service. Resource requirements are considered separately for the uplink and downlink. The high-level objective is to design a simple admission scheme that ensures adequate signal-to-interference ratios for both the incoming call (if accepted), as well as previously admitted calls. Our approach is based on two key ideas: 1) an integrated measure of resource utilization that is agnostic to the details of the traffic mix and 2) an estimate of the additional resources required to accommodate the new call seeking admission. The current work considers estimation of the total received power distribution on the uplink and the total transmitted power distribution on the downlink, and prediction of their displacements as a result of admitting a new call. The total received/transmitted power distributions are estimated based on data obtained from the power control module. The displacement of total received/transmitted power is predicted based on the characteristics of the incoming call and the current resource utilization. Dynamic call capacities are compared with static capacities to indicate the effectiveness of the proposed algorithm in achieving high network utilization with low probability of overload.
Keywords: CDMA system downlink; CDMA system uplink; QoS; Call admission control scheme; Call seeking admission; Code-division multiple-access wireless network; Dynamic call capacity; Power control; Quality of service; Radio resource management; Received power; Signal-to-interference ratio; Transmitted power